Testing the potential contribution of Wolbachia to speciation when cytoplasmic incompatibility becomes associated with host‐related reproductive isolation. Issue 10 (16th September 2021) - Bruzzese, Daniel J.; Schuler, Hannes; Wolfe, Thomas M.; Glover, Mary M.; Mastroni, Joseph V.; Doellman, Meredith M.; Tait, Cheyenne; Yee, Wee L.; Rull, Juan; Aluja, Martin; Hood, Glen Ray; Goughnour, Robert B.; et al.
Abstract: Endosymbiont‐induced cytoplasmic incompatibility (CI) may play an important role in arthropod speciation. However, whether CI consistently becomes associated or coupled with other host‐related forms of reproductive isolation (RI) to impede the transfer of endosymbionts between hybridizing populations and further the divergence process remains an open question. Here, we show that varying degrees of pre‐ and postmating RI exist among allopatric populations of two interbreeding cherry‐infesting tephritid fruit flies ( Rhagoletis cingulata and R . indifferens ) across North America. These flies display allochronic and sexual isolation among populations, as well as unidirectional reductions in egg hatch in hybrid crosses involving southwestern USA males. All populations are infected by a Wolbachia strain, w Cin2, whereas a second strain, w Cin3, only co‐infects flies from the southwest USA and Mexico. Strain w Cin3 is associated with a unique mitochondrial DNA haplotype and unidirectional postmating RI, implicating the strain as the cause of CI. When coupled with nonendosymbiont RI barriers, we estimate the strength of CI associated with w Cin3 would not prevent the strain from introgressing from infected southwestern to uninfected populations elsewhere in the USA if populations were to come into secondary contact and hybridize. In contrast, cytoplasmic–nuclear coupling may impede the transfer of w Cin3 if Mexican and USA populations were to come into contact. We discuss our results in the context of the general paucity of examples demonstrating stable Wolbachia hybrid zones and whether the spread of Wolbachia among taxa can be constrained in natural hybrid zones long enough for the endosymbiont to participate in speciation.